Dynamics of Communication from Perspective of Creativity in Group Theory - Girsang, Lasmery; Razali, Geofakta (COMMENTATE: Journal of Communication Management, 2023)
This research is a theory review of communications namely Creativity in Group Theory. This theory examines how the processes that appear in ideas, responses, processes or products, are new and relevant. To conduct this research, the authors apply a qualitative-descriptive method to dig detailed information from three informants as participants in Nata Academy’s training program. As the leader/owner of Micro, Small and Medium Enterprises (MSMEs), the informants run their business based on digital marketing. By running the observation and depth interview, authors analyze assumptions/concepts relating to creativity in groups done by the informants while joining a five months course. As the results, the authors find that all informants succeed in implementing creativity in forming, shaping, communicating and promoting the products through digital platforms. The creativity process emerges from brainstorming among the groups. Nevertheless, there are also constraints such as rigor and time pressure that can obstruct emerging creativity. Therefore, in conclusion, good group dynamics through digital marketing can support innovation and creativity. Besides that, through digital marketing, MSME as an aspect of growth in the economy must also be able to increase competitiveness by innovating and being creative.